Analisis sosiologikal terhadap pelaksanaan pemerintahan desa pada etnik Batak Angkola berasaskan adat Dalihan Na Tolu di Padang Lawas Utara - Siregar, Kondar (2017)
This study aims to identify the roles of Dalihan na Tolu (the three pillars of Batak philosophy) in managing village government, describe the consensus system in decision making and investigate the procedures of conflict resolution practiced at the village level in the Angkola Batak community in North Padang Lawas Regency, North Sumatra province, Indonesia. This study utilised a mix method approach using questionnaires and interviews. The data for this study were gathered from 200 respondents at four villages, namely Janji Matogu, Aek Godang, Padang Garugur and Suka Mulia. The findings show that the Batak Angkola community runs the village governments based on their cultural heritages also known as the Dalihan na Tolu on issues related to (a) recruitments of the civil servants, (b) consensus in decision making, and (c) the use of terms for village bodies, long before the implementation of acts on village government such as the Law of the Republic of Indonesia Concerning Village Number 6 of 2014 and other related regulations. The findings also indicate that the consensus on decision-making is based on the philosophy of Dalihan na Tolu has been applied at several levels, family consensus or Tahi Ungut-ungut; extended family consensus (kahanggi, anak boru and mora) or Tahi Dalihan na Tolu; consensus at village level or Tahi Godang Parsahutaon; and inter-villager compromise of Tahi Godang Haruaya Mardomu Bulung. Furthermore, the findings show that conflicts on village head election, appointments of village administrative staffs and fund distributions have been solved according to the following procedures, (a) submission of the report, (b) summon the parties for hearing, (c) separated hearings, (d) hearing with the parties concerned, (e) consensus in decision makings, and (f) recommend solution to the conflicting parties. The decision made by the village administrative authority should be complied by all parties concerned. The new findings of this study were the effectiveness of any regulations concerning village administration which was issued by the central administration in Jakarta can only be achieved if the the values of these regulations correspond to those of Dalihan na Tolu, the philosophy of Angkola Batak community.